Trajectories of Egyptian Women in the US - Tagen, Sageda A. (AUC Knowledge Fountain, 2026)
This thesis aimed at studying and analyzing the experiences of highly skilled Egyptian migrant women living in the US both who migrated as adults and those who migrated as children with their families. It analyzed their backgrounds prior to the migration decision, the migration decision and their legal status, the role of the family in their journey and their challenges within the social context of their workplaces. The study utilized a qualitative ethnographic lens. The study is based on ethnographic interviews with 15 highly skilled women living in the US, most of whom are concentrated in Indiana and Michigan. The research of this thesis contributes to the sectors of gender and feminist theories that addresses the experiences of highly skilled women while using Bourdieu’s theory of capital and habitus, focusing on the concept of transnational habitus, in analyzing the experiences of the women participants. The thesis covered the experiences of highly skilled Egyptian women in three main domains/ stations on their migration trajectory the visa status, the family life and workplace dynamics.